Strategi Guru Pendidikan Agama Islam dalam Menangani Kasus Juvenile Delinquency - Tri Anggraini Fitriana; Mohammad Zakki Azani (Journal on Education, 2023)
This research leads to cases of juvenile delinquency (Juvenile Delinquency) which became the beginning of the crime. This study discusses the formulation of the problem (1) Analyzing the perspective of PAI teachers on Juvenile Delinquency cases, (2) Strategies carried out by Islamic Religious Education teachers in dealing with Juvenile Delinquency cases, (3) The flow of handling carried out by PAI teachers in involving homeroom teachers, counseling teachers , and parents of students in dealing with Juvenile Delinquency cases. This research is a qualitative research that uses descriptive analytic data with the object of teachers and students at SMK Negeri 4 Klaten, the data obtained shows that the causes of juvenile delinquency occur from family, education, and the social environment. Thus the PAI teacher's strategy is to instill motivation and religiosity or Islamic values in students to strengthen their faith in dealing with juvenile delinquency cases, namely creating pleasant classroom conditions without tension, providing intensive scope factors, providing relevant character development outside of study hours. , and engage in mediation and monitoring with homeroom teachers, parents, students, and other teachers.